Cinnamic Acid, Ethanol and Temperature Interaction on Coumarate Decarboxylase Activity and the Relative Expression of the Putative Cd Gene in D. Bruxellensis - Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V; Salinas-Sanhueza, F (2011)
Sin Editorial Disponible